The Informative and Effective Approach towards Construction Contract Administration: A Modified Delphi Method - Chong, Heap Yih 261392G; Zin, R.; Lim, C.-C. (International Information Institute, 2011)
Every construction project tends to have contractual disagreements. A more informative and effective approach need to be considered to prevent or mitigate these contractual problems. The understanding of contract provisions needs to be reviewed, particularly on variations, which are the most litigious and problematic issues in the industry. Hence the research aims to administer the contract provisions on variations in a more clarified and resourceful manner, where a set of practical guidelines would be developed to enhance its understanding and contents of the related contract provisions. The results highlight a value added outcome, where the existing contract provisions are clarified using Plain English and also incorporated with additional information derived from the Delphi research. Eventually, the guidelines render a more understandable and informative reference that assists in decision-making.